Administrative Burden at the Community Empowerment, Village, Population and Civil Registration Services Village Management Sector Central Java Province, Indonesia - Tri Utami, Lies Norma; Zefanya Nathalieana Mellynda Haskoro (Arkus, 2024)
This study discusses the administrative burden on the Office of Community Empowerment, Village, Population, and Civil Registration (Dispermadesdukcapil), especially in the field of Village Planning. The method used in this study is empirical jurisprudence by examining policies that have been in effect and in reality, in people's lives. This study is oriented towards the basic data obtained directly from research conducted in the field, i.e., by interview data collection techniques. Each state administrative tool certainly has its own administrative burden, including the Village Planning Sector Dispermadesdukcapil, which consists of two sections, namely facilitation of village government regulation and evaluation of village development arrangement. The field of Village Planning has its own tasks and functions that focus on facilitating the regulation of the village government. In its implementation, the office issued several policies, and there are certainly obstacles experienced in various ways, both in facilitating regulation, budget, and other activities.